Estudo de representações, valores, normas e estilos dos jovens da cultura emo - Roamos Do Prado, Antonio (2012)
In the work of youth ministry today, the concern is how to get the Church and Pastoral to participate being part of the young person’s life project. For that, it is necessary to thoroughly understand the various juvenile realities, their interests, fears, doubts and anxieties. This is possible by performing a study and a thorough analysis of youth cultures. In this work, we chose a youth culture that attracts the attention of society by the way they react to the world. Generally, in a mysterious and hidden way, without so much fuss as if they really want to hide. And often there is a good reason for that. The youngsters of the Emo Culture suffer countless retaliations, frequently being victims of the homophobia generated by other youth cultures, or even veiled discrimination in the educational and, why not saying, pastoral environments.